(untitled) (Journal of Namibian Studies : History Politics Culture, 2025)
This article seeks to highlight the importance of the tourism sector and its role as a significant part in Economic development process, as tourism is considered a lever for economic growth in many countries of the world, and aims mainly to eradicate poverty through wealth creation, which significantly contributes in raising the standard of living of individuals, societies and communities in addition to improving their lifestyles, while also contributing to enhancing citizens’ awareness and their sense of belonging to their homeland. Tourism helps in the development of various economic sectors, including social, cultural and educational sectors, as well as improving international relations. After the concept of tourism was limited to trips and entertainment, it has become a human phenomenon and a basic social necessity in our modern era on which many countries of the world depend as an important economic source to support development, increase national income, expand productive bases, and create thousands of job opportunities.